Crescimento e nutrição mineral de Sida rhombifolia - Bianco, Silvano [UNESP]; Carvalho, L. S.; Bianco, Matheus Saraiva [UNESP] (Sociedade Brasileira da Ciência das Plantas Daninhas, 2014)
This experiment was carried out to analyze dry mass production and distribution, and the content and accumulation of macronutrients in arrowleaf sida (Sida rhombifolia) plants cultivated under mineral nutrition standard conditions. Plants grew in seven liter pots filled with sand substrate and daily irrigated with nutrient solution, under greenhouse conditions. Treatments consisted of times of evaluation (21, 35, 49, 63, 77, 91, 105, 119, and 133 days after emergence - DAE) and were arranged in a completely randomized design with four replicates. Arrowleaf sida plants showed small accumulation of dry mass (0.3 g per plant) and macronutrients (6.9 mg N per plant, 0.7 mg P per plant, 8.6 mg K per plant, 4.9 mg Ca per plant, 2,6 mg Mg per plant, and 0.3 mg S per plant) at the vegetative growth stage (< 49 DAE). Those accumulations increased, mainly after 63 DAE, and the daily accumulation rate was crescent up to 94 DAE (dry mass - DM), 89 DAE (N and P), 98 DAE (K), 95 DAE (Ca and S), and 93 DAE (Mg), when there was accumulation of 26.3 g DM per plant, 402.6 mg N per plant, 45.6 mg P per plant, 359.3 mg K per plant, 337.6 mg Ca per plant, 71.9 mg Mg per plant, and 20.9 mg S per plant. N and K had the highest rates and, consequently, were the most required and accumulated in greater amounts in plant tissues of arrowleaf sida.

O experimento foi conduzido com o objetivo de analisar a produção e a distribuição de massa seca e os teores e os acúmulos dos macronutrientes em plantas de guanxuma (Sida rhombifolia) cultivadas em condições padronizadas de nutrição mineral. As plantas cresceram em vasos de sete litros com substrato de areia, que foram irrigados diariamente com solução nutritiva e mantidos em condições de casa de vegetação. Os tratamentos corresponderam às épocas de avaliação (21, 35, 49, 63, 77, 91, 105, 119 e 133 dias após a emergência - DAE) e foram arranjados em delineamento experimental inteiramente casualizado com quatro repetições. As plantas de guanxuma apresentaram pequeno acúmulo de massa seca (0,3 g por planta) e de macronutrientes (6,9 mg N por planta; 0,7 mg P por planta; 8,6 mg K por planta; 4,9 mg Ca por planta; 2,6 mg Mg por planta; e 0,3 mg S por planta) na fase vegetativa (<49DAE). Esses acúmulos se intensificaram, principalmente, após 63 DAE; a taxa diária de acúmulo foi crescente até 94 DAE (massa seca - MS), 89 DAE (N e P), 98 DAE (K), 95 DAE (Ca e S) e 93 DAE (Mg), quando houve acúmulo de 26,3 g MS por planta, 402,6 mg N por planta, 45,6 mg P por planta, 359,3 mg K por planta, 337,6 mg Ca por planta, 71,9 mg Mg por planta e 20,9 mg S por planta. N e K foram os macronutrientes com maiores teores e, consequentemente, mais requeridos e acumulados em maior quantidade nos tecidos vegetais das plantas de guanxuma.
Growth and mineral nutrition of Sida rhombifolia
Keywords: guanxuma; planta daninha; crescimento; nutrição mineral; arrowleaf sida; weed; plant growth; mineral nutrition